Impact of pre‐ and post‐diagnosis physical activity on the mortality of patients with cancer: Results from the Health Examinees‐G study in Korea - Jaesung Choi; Joo‐Yong Park; Ji‐Eun Kim; Miyoung Lee; Kyuwan Lee; Jong‐Koo Lee; Daehee Kang; Aesun Shin; Ji‐Yeob Choi (Cancer Medicine, 2023)
Abstract Background Physical activity (PA) is recommended to improve the survival of cancer patients. However, the prognostic impact of specific PAs is not well understood. Therefore, we investigated the associations of the duration, type, intensity, and number of PAs one participates in pre‐ and post‐diagnosis with mortality in Korean patients with cancer. Methods Among the participants aged 40–69 years recruited from the Health Examines study, those diagnosed with cancer after baseline (n = 7749) and within 10 years before baseline (n = 3008) were included in the analyses for pre‐ and post‐diagnosis PA, respectively. Duration, intensity, type, and number of leisure‐time physical activities participated in were assessed using questionnaires. The Cox proportional hazard model was used to characterize the association between PA and cancer‐specific mortality, adjusting for demographics, behaviors, comorbidities, and cancer stage based on the Surveillance, Epidemiology, and End Results program. Results Pre‐diagnosis, patients participating in vigorous‐intensity activities (hazard ratio [HR]: 0.70, 95% confidence interval [CI]: 0.61–0.82), walking (HR: 0.85, 95% CI: 0.74–0.97), climbing (HR: 0.65, 95% CI: 0.55–0.77), sports (HR: 0.39, 95% CI: 0.25–0.61), and more than two activities (HR: 0.73, 95% CI: 0.63–0.86) had significantly lower all‐cause mortality. Importantly, these associations were only found in patients with colorectal cancer participating in vigorous‐intensity activities (HR: 0.40, 95% CI: 0.23–0.70). Post‐diagnosis, only patients who performed more than two activities (HR: 0.65, 95% CI: 0.44–0.95) had significantly lower all‐cause mortality. Similar associations were found for cancer mortality, both pre‐ and post‐diagnosis. Conclusion Specific characteristics of PA pre‐ and post‐diagnosis may influence the survival of cancer patients.